Estudo do comportamento das feições lineares observado em dados aeromagnéticos da Bacia do Paraná - MACHADO, Sérgio Augusto Moraes (Universidade Federal do Pará, 2014)
The digital image processing of aeromagnetic data has proved to be an excellent method of interpretation. This technique is referred to as the shaded relief method. The method was applied to aeromagnetic data, over part of the Parana Basin, to enhance the lineaments that are not clearly seen on the original magnetic-anomaly maps. To support our studies, we have used LANDSAT images, as many lineaments encountered in he basin are non-magnetic. This integration allowed definition of two dominant directions for the lineaments: N40° — 60°W and N40° — 65°E. With the definition of this pattern, we obtained some information about the geological trends and, hence, an idea about tectonic evolution of the basin. We also developed a procedure to compute the total magnetization vector of the principal lineament of the basin wich showed five different inclinations of the magnetization vector. These inclinations are explained by a superposition of induced magnetization effects, field reversal effects, and effects of anisotropic magnetization caused by demagnetization within the dikes.